2020
DOI: 10.1016/j.healun.2019.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment in pulmonary arterial hypertension: Insights from the GRIPHON study

Abstract: BACKGROUND: Approaches to risk assessment in pulmonary arterial hypertension (PAH) include the noninvasive French risk assessment approach (number of low-risk criteria based on the European Society of Cardiology and European Respiratory Society guidelines) and Registry to Evaluate Early and Long-term PAH Disease Management (REVEAL) 2.0 risk calculator. The prognostic and predictive value of these methods for morbidity/mortality was evaluated in the predominantly prevalent population of GRIPHON, the largest ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 17 publications
1
48
0
12
Order By: Relevance
“…In these patients PH diagnosis is usually difficult, because symptom progression can be subtle and early risk assessment is of paramount importance. [27][28][29] In such a population integration of parameters of LFT and echo seems reasonable. Integration of a greater number of variables into a prediction model of PH does not facilitate prediction due to the high interdependence of the factors.…”
Section: Discussionmentioning
confidence: 96%
“…In these patients PH diagnosis is usually difficult, because symptom progression can be subtle and early risk assessment is of paramount importance. [27][28][29] In such a population integration of parameters of LFT and echo seems reasonable. Integration of a greater number of variables into a prediction model of PH does not facilitate prediction due to the high interdependence of the factors.…”
Section: Discussionmentioning
confidence: 96%
“…Patients achieving all three low-risk criteria (WHO/ New York Heart Association FC I or II, 6MWD >440 m, and BNP <50 ng•L −1 or NT-proBNP <300 ng•L −1 ) had 2-, 3-and 5-year survival of 100%, 99% and 97%, respectively. This method has since been validated in data from the Phase 3 GRIPHON trial, which reported a 94% reduced risk of morbidity/mortality in patients with all three low-risk criteria versus those with no low-risk values [37].…”
Section: Bnp/nt-probnp and Comparison With Pulmonary Haemodynamics Ementioning
confidence: 99%
“…Steps to a novel composite endpoint The ability of the different risk assessment tools to discriminate not only between the different risk profiles but also between treatment arms was tested post-hoc in the PATENT-1 and -2, as well as in the GRIPHON and AMBITION studies. 30,[38][39][40] Three abbreviated versions of this risk stratification model were previously evaluated in patients with PAH in the French, Swedish and COMPERA registries. Application of the REVEAL risk score (RRS) to the PATENT study database showed similar results in terms of improvement and deterioration in favour of the verum group (riociguat), however a considerable placebo response during treatment appeared at 12 weeks.…”
mentioning
confidence: 99%